Extensive horse grazing improves grassland vegetation diversity, seed bank and forage quality of artificial embankments (Rhône River - southern France) - Moinardeau, Cannelle; Mesléard, François; Ramone, Hervé; Dutoit, Thierry (Journal for nature conservation, 2020)
•Low-intensity horse grazing creates species-rich patches of dry grasslands on embankments.•Horse grazing is positively linked to plant species-richness, seed bank density and forage values.•Co-existence of herbaceous and shrubby patches favours grazing sustainability. Grazing by herds of herbivores modifies plant communities in different ways, depending on the herbivore species. Horse grazing is already known to be effective in increasing plant diversity and maintaining herbaceous vegetation, creating different types of patches and thus ensuring spatial heterogeneity. On an artificial embankment at the Donzère-Mondragon hydroelectric facility in the Rhône Valley, extensive grazing by a rustic horse (Konik-Polski) was introduced several years ago to control shrub encroachment and to enhance plant grassland diversity. Vegetation monitoring surveys over a five-year period (2014–2018) showed that horse grazing maintained patches of open and short grasslands and increased species-richness, in particular of annual species, some of which have heritage value. In contrast, overly-low grazing pressure led to the dominance of an unpalatable perennial grass (Brachypodium phoenicoides) at the expense of the annual species that significantly enhance the forage value of the most heavily grazed patches. Horse grazing also had a positive impact on the permanent seed bank of the soil, increasing its heterogeneity and the density of viable seeds. Extensive horse grazing thus appears to be a relevant management tool to preserve the diversity and the forage quality of the most open and short grasslands. Nevertheless, grazing pressure here remained too low to allow restoration of grasslands already colonised by woody species. Combining different livestock species might be a better alternative to pure horse grazing, to increase heterogeneity and diversity. Our results are discussed in relation to extensive horse grazing on artificial ecosystems, such as the embankments bordering rivers and canals.